The Impact of Job Cadre on Psychological Wellbeing of Senior Citizens after Retirement – using Multivariate Analysis Approach: Key Findings & Policy Implications - Shah1, S Naqeeb Hussain; Shafiq , Mohammed; Ibrar, Mohammad; Munir, Akhtar (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed at assessing the psychological wellbeing and life satisfaction of senior citizens after retirement. This study is empirical in nature and employs the multivariate analysis approach to measure the impact of job cadre on mental health of retired elderly in Khyber Pakhtunkhwa province Pakistan. The conceptual design of this work is materialized by examining the significant relationship between the criterion variables and predictor variable. The dependent variable consists of multi-items standardized inventories, while the independent variable consists of various job categories. The result indicates that the combined dependent variable i.e. psychological wellbeing involving three outcome variables: self-esteem, life satisfaction, and perception about aging; is significantly influenced by the predictor variable. Further, the predictor variable has contributive qualities and strongly linked with the mental health and life satisfaction of senior citizens. The key findings and policy implications of this study are quite valuable for the government, policymakers, and donor agencies in devising the social welfare schemes for the betterment of senior citizens in Pakistan.